An Immune-Related Signature Predicts Survival in Patients With Lung Adenocarcinoma - Zhang, Minghui; Zhu, Kaibin; Pu, Haihong; Wang, Zhuozhong; Zhao, Hongli; Zhang, Jinfeng; Wang, Yan (Frontiers in Oncology, 2019)
Our objective was to investigate local immune status and its prognostic value in lung adenocarcinoma. A cohort of 513 lung adenocarcinoma samples from TCGA and ImmPort databases was collected and analyzed. The R package coxph was employed to mine immune-related genes that were significant prognostic indictors by both univariate and multivariate analyses. The R software package glmnet was then used for lasso cox regression analysis, and a prognosis prediction model was constructed for lung adenocarcinoma; clusterProfiler was selected for functional gene annotations and KEGG analysis. Finally, correlations between the RiskScore and clinical features or signaling pathways were established.Sixty-four immune-related genes were remarkably correlated with patient prognosis and were further applied. Samples were hierarchically clustered into two subgroups and those in each subgroup were different in terms of the distribution of race, age, tumor stage, receptor status, histological type, metastasis status, and patient prognosis. Based on this, the lasso regression algorithm was employed to screen the 14 most representative immune-related genes (PSMD11, PPIA, MIF, BMP5, DKK1, PDGFB, ANGPTL4, IL1R2, THRB, LTBR, TNFRSF1, TNFRSF17, IL20RB, and MC1R) with respect to patient prognosis. Then, the prognosis prediction model for lung adenocarcinoma patients (namely, the RiskScore equation) was constructed and the training set samples were incorporated to evaluate the efficiency of this model to predict and classify patient prognosis. Subsequently, based on functional annotations and KEGG pathway analysis, the 14 immune-related genes were mainly enriched in pathways closely associated with lung adenocarcinoma and its immune microenvironment, such as cytokine–cytokine receptor interaction and human T-cell leukemia virus 1 infection. Furthermore, correlations between the RiskScore and the clinical features of training set samples and signaling pathways (such as P53, cell cycle and DNA repair) were also demonstrated. Finally, the test set sample data were employed for independent testing and verification of the model.We established the prognostic prediction RiskScore model based on the expression profiles of 14 immune-related genes, which shows high prediction accuracy and stability in identifying immune features. This could provide clinical guidance for the diagnosis and prognosis of different immunophenotypes, and suggests multiple targets for precision lung adenocarcinoma therapy based on subtype-specific immune molecules.